Applicability of the flowing material balance method to heterogeneous reservoirs. (19th March 2022) - Han, Guofeng
Abstract: The flowing material balance (FMB) method is widely used to evaluate geological reserves because it does not require shut-in wells and uses daily production data. The original FMB method is based on a homogeneous medium model, but the reservoir is often heterogeneous. In this study, FMB equations are derived for radial composite reservoirs and naturally fractured reservoirs, and the effect of reservoir parameters on the estimation of geological reserves is analyzed. The study found that in order to obtain accurate geological reserves, the average formation total compressibility should be used. Inappropriate total compressibility may cause significant errors. Finally, the proposed method is validated by a case study.